Evaluation of Patient Discharge Information Between What Is Said and What Is Written - Suha Tailakh; Muayyad Mustafa Ahmad (ACHSM, 2023)
Background: Patients' discharge from the hospital is considered a crucial transition. Appropriate patient education about their condition and its treatment can reduce adverse events and improve health outcomes. Objective: Identifying high-risk patients for adverse events after hospital discharge and evaluating patient discharge information to ensure patients are safely discharged. Method: Between January 2019 and February 2020, a retrospective cross-sectional study examined hospital discharge notes. A random sample of 600 hospital discharges was audited, and a convenience sample of 150 patients was used to gauge patient satisfaction. Results: The patient's age, medical history, the presence of a physical limitation, and the presence of a surgical wound were all significantly related to readmission at p < .05. In addition, there was a significant correlation between emergency room visits, medical history, and physical or mental impairment p< .05. Lastly, the presence of complications was associated with physical restriction and surgical wound p < .05. The findings revealed that84.6% (n = 127) of patients did not appear to pay attention to the information on their discharge summaries, but they kept them as a reminder of their follow-up appointments. There were medical abbreviations in all of the discharge summaries (n = 150). Almost all discharge summaries contained at least 70% of the required information (diagnosis, past history, allergies, procedures, laboratory results, medications, and appointments). In contrast, the patients' level of satisfaction was lowest with respect to crucial aspects such as warning signs, recommendations, and educational materials. They were neither verbally nor in writing summarized. Conclusion: Patient-specific discharge information and summaries should be provided. It should be suitable for the patients' physical, educational, and psychological conditions. Important parts of post-discharge instructions should be provided in a straightforward, written format to improve health outcomes and reduce adverse events.